REQUIREMENTS FOR QUALITY AND SAFETY RECORDS OF PATIENTS - Moraes, Margarete Farias de (Informação em Pauta, 2018)
The health services perform an intricate system of processes, assistance, technical support, logistical and administrative support. These processes require inputs and resources to give the expected result, such as specific materials and equipment and especially people, in addition to an adequate physical structure. Good practices and methods are also central to sustaining these processes. We can identify the importance of various management and control processes for quality assurance and health security, such as "Registration and handling of customer complaints", "Registration and handling of failures", "Satisfaction survey", "Management of indicators "," Critical review “, “Case review ", as well as "quality management and patient information security". This article intends to present and discuss the processes of quality and safety management of patient information, based on the standards contained in the Manual Brasileiro de Acreditação. The qualitative analysis of a set of requirements of the Information and Communication Management standard of the Manual Brasileiro de Acreditação was used as a method, as well as presenting concepts about health quality and safety. The work noted the importance of this standard for the management of information services and units.